2022
DOI: 10.3390/nano12091517
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking and Distribution of Cd and InP Quantum Dots in HeLa and ML-1 Thyroid Cancer Cells

Abstract: The study of the interaction of engineered nanoparticles, including quantum dots (QDs), with cellular constituents and the kinetics of their localization and transport, has provided new insights into their biological consequences in cancers and for the development of effective cancer therapies. The present study aims to elucidate the toxicity and intracellular transport kinetics of CdSe/ZnS and InP/ZnS QDs in late-stage ML-1 thyroid cancer using well-tested HeLa as a control. Our XTT (2,3-bis-(2-methoxy-4-nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…According to the manufacturer, this quantum dot product has an emission peak of 620-635 nm. Previously, Zhang et al (our lab) measured an air-dry diameter of around 5-10 nm and a hydrodynamic diameter of 20 nm [84]. These numbers were consistent with the manufacturer's provided information.…”
Section: Cdse/zns Qd Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…According to the manufacturer, this quantum dot product has an emission peak of 620-635 nm. Previously, Zhang et al (our lab) measured an air-dry diameter of around 5-10 nm and a hydrodynamic diameter of 20 nm [84]. These numbers were consistent with the manufacturer's provided information.…”
Section: Cdse/zns Qd Characteristicssupporting
confidence: 86%
“…These are proteins that are associated with transcription, translation, mitochondrial function, and vesicular trafficking. QD treatment has previously been shown to have a negative impact on many cellular processes and components, especially vesicular trafficking and mitochondrial function [39,67,[83][84][85][86][87][88][89]. Thus, future research that focuses on the interaction between these proteins with QDs and its impact on protein structure and function may open a novel aspect to learning about QD toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, scientists found that mammalian cell lines could uptake the QDs efficiently. QDs are targeted to different cellular organelles [28][29][30]. According to these mentioned features, QDs show their potential in drug delivery.…”
Section: Qds In Drug Deliverymentioning
confidence: 99%
“…Simultaneously, QDs’ fluorescence is easily detectible, allowing researchers to clearly map the drug distribution process of QD-derived delivery complexes. Moreover, it was found that QDs are easily taken up by various mammalian cell lines and are targeted to different cellular organelles, including the lysosome [ 114 , 115 , 116 , 117 ]. This feature of QDs ensures that QD-derived drug delivery systems are able to enter targeted cells and use the acidic environment in acidic organelles to dissociate therapeutic drugs from the delivery vehicle.…”
Section: Drug Deliverymentioning
confidence: 99%